Corrosion behaviour of mild steel in aqueous acetic acid solutions containing different amounts of formic acid - Singh S.K.; Mukherjee A.K.; Singh M.M. (My University, 2025)
The kinetics of mild steel corrosion in 20:0, 19:1, 18:2 and 15:5 (v/v%) aqueous mixture of acetic and formic acids has been investigated by weight loss and potentiostatic polarization techniques. The effects of composition of electrolyte and temperature on the corrosion rate of mild steel have been evaluated. The corrosion rate of mild steel increased linearly with temperature as well as amount of formic acid in the mixture. Anodic polarization curves exhibited active nature over the whole range of potential at each composition and temperature. Addition of sodium acetate to the mixture led to the transition from active to active-passive-transpassive behaviour in the solutions having lower concentration of formic acid. On replacing sodium acetate by sodium formate, and sodium sulphate, no change in the nature of polarization behaviour is observed.